What motivates rural teachers to retain? A study on Chinese rural teachers' turnover from grounded theory and FsQCA - Cheng, Chao; Diao, Yanjie; Ding, Xing (Frontiers in Psychology, 2023)
This research is aim at a deeper understanding of factors that leading Chinese rural teachers' (CRTs) turnover in their profession. The study regarded in-service CRTs (n = 408) as the participants, adopted the semi-structured interview and an online questionnaire to collect the data, and used grounded theory and FsQCA to analysis the data based. We have found that (A) welfare allowance, emotional support, and working environment can be substituted equivalently to increase CRTs' retention intention while professional identity regarded as the core condition; (B) career development is neglected for two reasons: one is CRTs compensated for inadequate social support by self-improvement; another is CRTs adapted themselves to accept professional stagnation; (C) the CRTs will have a strong intention to retain but lack enthusiasm for teaching because lack professional identity when the external environment is favorable. This study clarified the complicated causal relationships between CRTs' retention intention and its factors, contributed to the practical development of CRTs workforce.